Leasehold Payments from the Perspective of the Hungarian Chamber of Agriculture - Fekete, Kristóf (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2024)
In this study, the author presents and analyses the proportionality examination of leasehold contracts in the light of recent legislative changes from the viewpoint of the Hungarian Chamber of Agriculture, in this framework, the paper also deals with the practice of the agricultural administrative bodies. Starting from the relevant constitutional and statutory provisions, the study describes, through pragmatic examples, the obligations and possibilities of the Hungarian Chamber of Agriculture regarding the disproportionality of leasehold payments, as well as its emerging practice. The study concludes that the Hungarian Chamber of Agriculture is real support for agricultural administrative bodies in their procedures for determining the disproportionality of leasehold payments and that their decisions can reflect the value and interests of agriculture, as enshrined in law.